2002
DOI: 10.1080/02656730110088373
|View full text |Cite
|
Sign up to set email alerts
|

Cell killing of melanoma B16 in vivo by hyperthermia and cytotoxins

Abstract: The aim of this study was to investigate antitumour activity of cisplatin, dacarbasine, cyclophosphamide and a new compound from the nitrosourea group--acetamido-CNU ((2-chloroethyl)-1-nitroso-3-(methylenecarboxamido)-urea)--applied with or without local hyperthermia (43.5 degrees C/60 min). The tumour model for the investigation of antitumour activity was a mouse melanoma B16 transplanted into the footpad. Dacarbasine, cyclophosphamide and acetamido-CNU applied as a single treatment had statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…DTIC, an alkylating agent that inhibits purine synthesis [14] has long been applied against malignant melanoma development. Regimens such as the Dartmouth regimen and CVD regimen to combine the application of anticancer compounds are widely used in the therapy of malignancies [15,16]. The suggested combination dosage of DTIC and CDDP is one of the most recognised modality among them [17].…”
Section: Discussionmentioning
confidence: 99%
“…DTIC, an alkylating agent that inhibits purine synthesis [14] has long been applied against malignant melanoma development. Regimens such as the Dartmouth regimen and CVD regimen to combine the application of anticancer compounds are widely used in the therapy of malignancies [15,16]. The suggested combination dosage of DTIC and CDDP is one of the most recognised modality among them [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of hyperthermia have focused on two commonly applied strategies, conventional hyperthermia at mild temperatures (42–45°C) (1,20,21) and ablation therapy at high temperatures (>70°C) (22). To the best of our knowledge, no study has examined the difference in antitumor effects between mild (42–45°C) and high temperatures (>70°C) under the same conditions as performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a superficial tumor, melanoma can easily be administered local hyperthermia from the clinical point of view. Either as a monotherapy or as an adjuvant therapy with other treatments, such as chemotherapy or radiotherapy, the results of hyperthermia treatment from clinical trials and in vivo studies are encouraging, suggesting a promising protocol for malignant melanoma (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies have shown that malignant melanoma may be even more sensitive to temperature (8,9). Studies of hyperthermia have been focused on two commonly applied strategies: conventional hyperthermia at mild temperatures (42-45˚C) (6,8,9) and ablation therapy at high temperatures (>70˚C) (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation